Tooth Loss in a Young Population from South Brazil - Cristiano Susin, DDS, MSD, PhD; Alex N. Haas, DDS, MSD; Rui V. Opermann, DDS, PhD; (Blackwell Synergy, 2006)
To assess the prevalence, extent, and risk indicators of tooth loss in a representative young urban population from south Brazil.